Фотоприемники ультрафиолетового излучения на основе тонких пленок ZnS - Bobrenko, Yu. N.; Yaroshenko, N. V.; Sheremetova, G. I.; Semikina, T. V.; Atdaev, B. S. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
High efficient photodiodes on the base of р-Cu1,8S/n-ZnS/(ZnS)х(CdSe)1–х/CdSe/Mo-structure with variband interlayer were fabricated. Optimization of this layer thickness was shown to be efficient method of reduction of photosensitivity behind UV region while preserving one in UV region.